2022
DOI: 10.13189/ujaf.2022.100501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tax Rate on Taxpayers' Voluntary Compliance in Tanzania

Abstract: the practical implication of the result indicated that the tax rate associated with tax is very high that affect the non-tax compliance, while the social implication of the study is that high tax rate causes the government to lose revenue and hence diminishes the efforts of providing social services to the citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The findings revealed that tax rate has negative influence on tax compliance where by the less the tax rate imposed will influence SMEs to tax compliance and also imposing high tax rate to the SMEs will contribute to non-tax compliance in Iringa Municipality where the findings are supported by Chindengwike and Kira (2022) who examined the effect of tax rate on taxpayers' voluntary compliance in Tanzania, where finding shows that there is a negative effect of the tax rate on taxpayers' voluntary compliance. Again, the study indicates that the presence of good tax rates improves taxpayers' voluntary compliance and the tax rates influence taxpayers' voluntary compliance.…”
Section: Contribution Of Tax Rate To Tax Compliance Among Smes In Iri...mentioning
confidence: 84%
“…The findings revealed that tax rate has negative influence on tax compliance where by the less the tax rate imposed will influence SMEs to tax compliance and also imposing high tax rate to the SMEs will contribute to non-tax compliance in Iringa Municipality where the findings are supported by Chindengwike and Kira (2022) who examined the effect of tax rate on taxpayers' voluntary compliance in Tanzania, where finding shows that there is a negative effect of the tax rate on taxpayers' voluntary compliance. Again, the study indicates that the presence of good tax rates improves taxpayers' voluntary compliance and the tax rates influence taxpayers' voluntary compliance.…”
Section: Contribution Of Tax Rate To Tax Compliance Among Smes In Iri...mentioning
confidence: 84%
“…Incentives are given to citizens who comply with tax obligations as appreciation and encouragement. According to Chindengwike & Kira (2022), tax rates affect attendance levels. A higher public willingness to pay taxes leads to a better tax ratio (Chindengwike & Kira, 2022).…”
Section: Tax Administration Reformmentioning
confidence: 99%
“…According to Chindengwike & Kira (2022), tax rates affect attendance levels. A higher public willingness to pay taxes leads to a better tax ratio (Chindengwike & Kira, 2022).…”
Section: Tax Administration Reformmentioning
confidence: 99%
“…However, the study by Bernard et al, (2019), focused on costs and its implication on tax compliance and failed to link tax code complexity to tax compliance as is the case in the current study. Chindengwike and Kira (2022) researched on the effect of tax rate on taxpayers' voluntary compliance in Tanzania. A cross-sectional survey research design technique was used.…”
Section: Tax Filing Procedures and Tax Compliancementioning
confidence: 99%